HIV type 1 Gag virus-like particle budding from spheroplasts of Saccharomyces cerevisiae - Sakuragi, Sayuri (The National Academy of Sciences, 2002)
Expression of retroviral Gag protein in yeast has previously shown Gag targeting to the plasma membrane but little or no production of Gag virus-like particles (VLPs). Here we show that, after removal of the cell wall, the expression of HIV type 1 Gag protein in Saccharomyces cerevisiae spheroplasts allowed simultaneous budding of VLPs from the plasma membrane. Our data show that (i) the VLPs released from yeast spheroplasts were spherical and had morphological features, such as membrane apposed electron-dense layers, characteristic of the immature form of HIV particles; (ii) the VLPs were completely enclosed in the plasma membrane derived from yeast, which is denser than that of higher eukaryotic cells; (iii) the VLP Gag shells remained intact after treatment of nonionic detergent; and (iv) the VLPs were released soon after removal of the cell wall and accumulated up to 300 μg/liter of culture. Our results also show that VLP production was abolished by amino acid substitution of the Gag N-terminal myristoylglycine and impaired when Gag C-terminal deletions were extended beyond the nucleocapsid domain. These results were consistent with those obtained previously in higher eukaryotic expression systems, suggesting that similar Gag domains were used for VLP assembly. We suggest that the system described here offers significant advantages for studying host factors required for VLP budding. The system also may be available for production of vector virus-free VLPs for practical applications such as vaccine development.